HIV-1 protease, Gag and gp41 baseline substitutions associated with virological response to a PI-based regimen. (14th February 2019) - Perrier, Marine; Castain, Louise; Regad, Leslie; Todesco, Eve; Landman, Roland; Visseaux, Benoit; Yazdanpanah, Yazdan; Rodriguez, Christophe; Joly, Véronique; Calvez, Vincent; Marcelin, Anne-Geneviève; Descamps, Diane; et al.
Abstract: Objectives: To assess, at ART initiation, the impact of baseline substitutions in protease, Gag and gp41 regions on the virological response to a first-line PI-based regimen. Patients and methods: One hundred and fifty-four HIV-infected ART-naive patients initiating a PI-based regimen including darunavir ( n =  129) or atazanavir ( n =  25) were assessed, including 36 experiencing virological failure (VF). Whole pol, gag and gp41 genes were sequenced at ART baseline by ultra-deep sequencing (UDS) using Illumina ® technology. Supervised data-mining analyses were performed to identify mutations associated with virological response. Structural analyses were performed to assess the impact of mutations on protease conformation. Results: UDS was successful in 127, 138 and 134 samples for protease, Gag and gp41, respectively (31% subtype B and 38% CRF02_AG). Overall, T4A and S37T mutations in protease were identified as being associated with VF ( P =  0.02 and P =  0.005, respectively). Among CRF02_AG sequences, I72M and E21D mutations were associated with VF ( P =  0.03 for both). They all induced some conformational changes of some protease side-chain residues located near mutated residues. In Gag, mutations associated with VF were G62D, N315H and Y441S ( P =  0.005, P =  0.007 and P =  0.0003, respectively). All were localized outside Gag cleavage sites (G62D, matrix; N315H, capsid; and Y441S, p1). In gp41, the I270T mutation, localized in the cytoplasmic tail, was associated with VF ( P =  0.003), and the I4L mutation, in the fusion peptide, was associated with virological success ( P =  0.004). Conclusions: In this study, new baseline substitutions in Gag, protease and g41, potentially impacting PI-based regimen outcome, were evidenced. Phenotypic analyses are required to confirm their role in the PI-resistance mechanism.